Courtney Wells: capstone - Wells, Courtney, artist (Colorado State University. Libraries, 2017)
The artist's statement: Focusing on aspects of the human condition in correlation to intimate relationships with one another, my work comments on the psychological and subconscious processes that impact how we interact with each other. A common interaction that people struggle with is intimacy and vulnerability. From research done, people start to feel uncomfortable in their personal space if a person encroaches within 18 inches of their body, depending on the relationship. My studies involve the figure and that uncomfortable space that can at times feel heavy, dense, and sometimes empty. The interaction (or lack there of) within the figures of my pieces represent the uncomfortable feeling of intimacy and the intimidation of being vulnerable within those 18 inches physically and/or mentally. My pallet choice comes from the duality of the good and bad aspects of being close to someone. The intense passion yet fragility of being vulnerable. Red can be passionate but also signify anger. Blue can be calm but also melancholy. Painting is an intimate process within itself. The psychological aspect of my work reflects in the nonverbal communicative elements. My figures' facial expressions, gestures, and the vignette of flowers indicate this nonverbal discomfort with closeness. In some cultures, peonies symbolize bashfulness and shame in regards to intimacy. Peonies have become a common theme in my life since childhood; in the month of May, they blossom every year in my grandparents' garden. With holding this symbol near and dear to me, it has become a motif within my work to give a personal lens of these feelings.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting; oil on canvas